1994
DOI: 10.1103/physreva.50.2719
|View full text |Cite
|
Sign up to set email alerts
|

Antimode dynamics and chaotic itinerancy in the coherence collapse of semiconductor lasers with optical feedback

Abstract: Low-frequency fluctuations observed in the coherence collapse of semiconductor lasers are numerically investigated based on the Lang-Kobayashi model. It is found that the attractor in the compound cavity mode loses its stability due to a crisis with an antimode. Chaotic itinerancy among the destabilized compound cavity modes is also found.PACS number(s): 42.50. Ne, 42.55.Px, 42.60.Mi, 05.45.+b

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
119
0
11

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(149 citation statements)
references
References 19 publications
6
119
0
11
Order By: Relevance
“…The upper half of the fixed points on the ellipse, denoted by stars, all exhibit a saddle-node instability and can be regarded as the destructive interference solutions in the passive case. They are often called antimodes [14]. The other fixed points, denoted by open circles, can be regarded as the constructive interference solutions in the passive case.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The upper half of the fixed points on the ellipse, denoted by stars, all exhibit a saddle-node instability and can be regarded as the destructive interference solutions in the passive case. They are often called antimodes [14]. The other fixed points, denoted by open circles, can be regarded as the constructive interference solutions in the passive case.…”
mentioning
confidence: 99%
“…Sano [14] was the first to recognize the role of the antimodes in LFF and proposed that LFF is a form of chaotic itinerancy [3] among the attractor ruins of the destabilized compound cavity modes, where each dropout is associated with the trajectory approaching too close to one of the (many) antimodes. It was shown by Van Tartwijk, Levine, and Lenstra [15] that on each attractor ruin the power is organized in irregular pulses.…”
mentioning
confidence: 99%
“…We speculate that the observed dark pulse is a kind of temporal cavity soliton formed in the laser. Semiconductor lasers subject to optical feedback from an external mirror have been extensively investigated both theoretically [1][2][3] and experimentally. 4,5 It has been shown that as a result of the delayed feedback, the lasers can exhibit a variety of interesting features, including the destabilization of relaxation oscillations, 6-9 coherence collapse, 10 and low-frequency fluctuations (LFF) or dropouts.…”
mentioning
confidence: 99%
“…4,5 It has been shown that as a result of the delayed feedback, the lasers can exhibit a variety of interesting features, including the destabilization of relaxation oscillations, 6-9 coherence collapse, 10 and low-frequency fluctuations (LFF) or dropouts. 1,11 Physically, a nonlinear system with delayed feedback has infinite solutions, whose behaviors need to be explained in terms of the nonlinear dynamics. Theoretical studies on the semiconductor lasers with delayed feedback based on the Lang-Kobayashi (LK) equations 2 or their simplfied form 12 have shown that multiple attractors can coexist in the system.…”
mentioning
confidence: 99%
“…Noise-driven models have been proposed to describe the LFF effect [3]. A deterministic approach, based on the single mode Lang-Kobayashi (LK) equations [4], was proposed in [5] to explain the LFF as a chaotic itinerancy with a drift [6]. Recently, there have been strong indications that the LFF need not be irregular: the laser can produce a train of equally spaced pulses [7].…”
mentioning
confidence: 99%